Impact of reduced tillage and crop residue management on soil properties and crop yields in a long-term trial in western Kenya - Okeyo, Jeremiah M.; Norton, Jay; Koala, Saidou; Waswa, Boaz Shaban; Kihara, Job Maguta; Bationo, B. André (Commonwealth Scientific and Industrial Research Organisation, 2016)
Sustainable farming practices are required to address the persistent problems of land degradation and declining crop productivity in Sub-Saharan Africa. Approaches such as reducing tillage and retaining crop residues as mulch are potential entry points for smallholder farmers to move towards sustainability. In this study, we assessed the impact of reduced tillage (RT) compared with conventional tillage (CT), each combined with crop residue reapplication, on soil quality indicators and crop yields under an 8-year trial in western Kenya. Our results indicate that RT combined with crop residue reapplication enhanced soil physical quality through increased macroaggregate (>2000µm) proportions and mean weight diameter. Similarly, lower respiratory quotient values indicate that soil microbes under RT have better substrate-use efficiency than those under CT. Nevertheless, soil organic carbon (C), potentially mineralisable C, microbial biomass C and mineral nitrogen contents were all higher under CT with crop residue incorporated into the soil. Maize grain yield and aboveground biomass were also higher under CT. Thus, despite RT showing potential to improve soil physical properties, CT performed better. A stepwise approach is proposed towards the practice of conservation agriculture under resource-constrained smallholder farming conditions, starting with increased biomass production to provide crop residue for soil cover, followed by RT approaches.